ANALISIS NILAI CT-NUMBER PADA CT-SCAN THORAX DENGAN KASUS COVID-19 - Gede Dharma Putra; I Putu Eka Juliantara; I Made Lana Prasetya (Perhimpunan Radiografer Indonesia (PARI), 2022)
Background : Computed Tomography (CT) scanner is an imaging tool used to obtain images of certain parts of the body using X-rays. CT-Scanner more detailed image, compared to X-ray, CT Number is the value of the X-ray attenuation coefficient (energy attenuation) determined by the average X-ray calculated in Hounsfield Units (HU) which is a standard facility that always is on the CT-Scan plane. Thorax CT-Scan is a radiological examination technique to obtain anatomical information of cross-sectional slices such as axial, coronal and sagittal. Coronavirus Disease 2019 (Covid-19 ) is an infectious disease caused by a species of coronavirus, namely severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). As a recent study, the CT-Scan abnormality that is most often observed in Covid-19 patients is ground glass opacity (GGO). Methods : This research uses descriptive quantitative with an observational approach. This measurement uses the Region Of Interest (ROI) to determine the value of the CT Number, where the Region Of Interest (ROI) is directed at the picture that contains a pathological abnormality of Grond Glass Opacity (GGO) on the CT-Scan Thorax in cases of Covid-19 then the CT Number value is compared with results of research conducted by Ali & Ghonymy, (2020). Result and Coclusion : Shows that there is a range of CT Number values ​​using quartile 3 or 75% percintile with the result of : -167 HU, Maximum : -74 minimum value : -288 HU. This means that it is a pathological Grond Glass Opacity (GGO) for Covid-19 patients.